2011
DOI: 10.1016/j.aquatox.2011.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration, metabolism and excretion of triclocarban in larval Qurt medaka (Oryzias latipes)

Abstract: The antimicrobial triclocarban (TCC) is frequently found in personal care products and commonly observed in surface waters and sediments. Due to its long environmental persistence TCC accumulates in sewage sludge. It also shows a high unintended biological activity as a potent inhibitor of the soluble epoxide hydrolase (sEH) and may be an endocrine disruptor. In this study, we investigated bioconcentration, metabolism and elimination of TCC in fish using Medaka (Oryzias latipes) as a model. Medaka larvae (7±1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 34 publications
4
39
1
Order By: Relevance
“…Thus, conjugation with glucuronic acid plays a key role in both renal and biliary elimination of TCC. In a recent study, it was also shown that glucuronides of phase I metabolites are the major metabolites in fish (Schebb et al, 2011a). However, no information is available about the UDP-glucuronosyltransferases (UGTs) involved in the conjugation of TCC and its metabolites, as well as the biochemistry and kinetics of the conversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, conjugation with glucuronic acid plays a key role in both renal and biliary elimination of TCC. In a recent study, it was also shown that glucuronides of phase I metabolites are the major metabolites in fish (Schebb et al, 2011a). However, no information is available about the UDP-glucuronosyltransferases (UGTs) involved in the conjugation of TCC and its metabolites, as well as the biochemistry and kinetics of the conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Rats received a dose of 1 mg/kg b.wt., and mice received a dose of 5 mg/kg b.wt. After administration, urine was collected between 0 to 24 and 24 to 48 h. Urine was analyzed using online-LC-MS, as described previously (Schebb et al, 2011a).…”
mentioning
confidence: 99%
“…Due to its lipophilicity, TCC bioconcentrates in the aquatic environment and is one of the most abundant anthropogenic compounds found in sewage sludge (Langford et al, 2011). Moreover, significant TCC bioconcentration in aquatic organisms such as algae, snails (Coogan et al, 2007;Coogan and La Point, 2008), and fish (Schebb et al, 2011a) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The main phase 1 metabolites in all species are monohydroxylated-TCC derivatives bearing the hydroxyl group ortho to the aniline group, namely 29-OH-TCC and 69-OH-TCC (Birch et al, 1978;Baumann et al, 2010;Schebb et al, 2012b). In addition, hydroxylation in the meta position (39-OH-TCC) and substitution of a chlorine atom by a hydroxyl group occurs, yielding 3,4-dichloro-49-hydroxycarbanilide (DHC) [for the structures of metabolites see Schebb et al (2011a)]. All hydroxylated metabolites undergo extensive phase II conjugation by UDP-glucuronosyl transferases (Schebb et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining proportion of the total loss was shared by the advection export. It is likely that a certain percentage of the target chemicals can accumulate in aquatic organisms, 15,19,43,[49][50][51] as found in the multimedia model for the sh. However, without adequate vegetation and aquatic biota quantity data, the current model failed to catch the inuence of biological accumulation.…”
mentioning
confidence: 99%